Phytosociological characteristics of Quercus cerris L. forests in east Slaviona (Croatia) - Franjić, Josip; Škvorc, Željko; Filipović, Krunoslav; Vitasović Kosić, Ivana (Hacquetia, 2015)
The following paper reports on the results of phytosociological research on Slavonian Quercus cerris forests in the woodlands of Zokovica – Đakovo and Cerik – Vučevci near Đakovo. 20 relevés were recorded in accordance with the Braun-Blanquet classical method. The relevés were set against the already published relevés of thermophilous forests of Carpino betuli-Quercetum roboris quercetosum cerris from the area of east Slavonia, and numerical analysis was performed. The studied Quercus cerris forests had developed through anthropogenic degradation of the association Carpino betuli-Quercetum roboris quercetosum cerris or Carpino betuli-Quercetum roboris typicum. Both of these stages of degradation have not been phytosociologically studied enough and have not received a defined syntaxonomic status. Conditions of the habitat have changed so much in a degraded ass. Carpino betuli-Quercetum roboris quercetosum cerris, that urgent efforts ought to be put into the attempt to reintroduce Quercus robur into the stands. These stands are described as an association of Aceri campestri-Quercetum cerris ass. nova. It would require far less work to reintroduce the Quercus robur into degraded forests of association Carpino betuli-Quercetum roboris typicum, where habitat conditions have not been changed to a greater extent.